2023
DOI: 10.2147/ppa.s350753
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab for the Treatment of Psoriasis in Pediatrics: Patient Selection and Acceptability

Abstract: Psoriasis (PsO) is a chronic, systemic, immune-mediated inflammatory skin disease affecting 1% to 5% population worldwide. In one-third of patients, the first symptoms of PsO manifest in childhood, with a mean age of nine years. Psoriasis in children under 16 years of age constitutes 4% of dermatological problems in this age group. Chronic inflammation of the skin observed in PsO is associated with a development of potentially serious comorbidities, including psoriatic arthritis, hypertension, metabolic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It could allow them to better handle depression, anxiety and other emotions caused by physical, psychological and social frailty. 4 If an elderly patient who suffers from high physical frailty due to diabetes remains in a state of stress and seldom receives social support from family, friends and society, they will be unwilling to communicate with others, raising their SPB level. Hence, it is imperative not only to secure the material foundation but also to empower individuals to exercise subjective initiative in alleviating (SPB).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could allow them to better handle depression, anxiety and other emotions caused by physical, psychological and social frailty. 4 If an elderly patient who suffers from high physical frailty due to diabetes remains in a state of stress and seldom receives social support from family, friends and society, they will be unwilling to communicate with others, raising their SPB level. Hence, it is imperative not only to secure the material foundation but also to empower individuals to exercise subjective initiative in alleviating (SPB).…”
Section: Discussionmentioning
confidence: 99%
“…2 Self-perceived burden (SPB) refers to negative emotions such as anxiety, depression and loneliness, which are caused by physical worries about the illness and psychological stress that encompasses feelings of guilt, dependence and fear of imposing a burden on others during the care-receiving process. 3 Recent studies 4 have shown that the frailty arising from chronic diseases among elderly patients is in close connection with SPB. Frailty is a senile syndrome mainly characterised by decreased physiological reserve function, multiple organ dysfunction, increased organismal vulnerability and declining anti-stress ability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, secukinumab resulted in a 48% decrease in the Ichthyosis-Area-Severity-Index score following a 6-month therapy term in a young patient with severe erythrodermic Ichthyosis associated with ABCA12 deficiency in a therapeutic trial. Treatment was well tolerated, and the patient's blood cytokine profile consistently changed, showing a decrease in proinflammatory cytokines and a Th17-skewing (Albela et al, 2024;Narbutt et al, 2023;Yogarajah et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, secukinumab was approved for the treatment of moderate to severe plaque psoriasis in pediatric patients above 6 years of age. 8 Nevertheless, there was a dilemma concerning the initiation of biological therapy as it may lead to heightened vulnerability to infections or exacerbate autoimmune processes, potentially resulting in paradoxical inflammation or even triggering autoimmune disease. 9 We have previously encountered a situation where we administered adalimumab to patient with immunodeficiency as a part of DiGeorge syndrome and uncontrolled juvenile idiopathic arthritis.…”
mentioning
confidence: 99%